Literature Review : Teori-Teori Kepemimpinan: (Modern dan Tradisional) - Susan Febriantina; Calvin Kimura; Hana Nurkhairani; Muhammad Fajar Bayu Wicaksono; Pradipta Afrah Nugraha; Safrina Primadhita (Journal of Student Research, 2025)
Traditional and modern leadership are two approaches with distinct characteristics and advantages. Traditional leadership is rooted in culture, customs, and values passed down through generations, where the leader's legitimacy is often based on lineage, social status, or collective recognition within the community. This model emphasizes hierarchy, authority, and stability to maintain group harmony. However, in a constantly changing era, the traditional approach is often deemed less flexible as it tends to be static and resistant to adaptation. In contrast, modern leadership emerges in response to the needs of more dynamic and complex societies and organizations. Modern leaders prioritize competence, innovation, and member empowerment, emphasizing effective communication and the ability to adapt to change. Both approaches hold unique relevance in different contexts. Integrating the positive values of traditional and modern leadership can create a more holistic model of leadership aligned with contemporary demands.